Conceptualization and Measurement of Human Resources Management Systems Functional Flexibility (International Journal of Innovative Research in Engineering & Management, 2021)
The literature does not yet explicitly explain practical  flexibility, despite its strategic relevance. Empirical  investigations have reached different and often opposing  findings based on several concepts and measurement  methodologies. This study proposes a structure to define and  measure functional flexibility in the field of human resource  management. By classifying previous definitions as well as  causative in the process, we will try to understand this word.  In the first part of this essay we examine and argue the  necessity for some practical flexibility in the administration of  human resources operations, which helps the company adjust  to changing environments. From this point of view, this talent  is seen as an important source of competitive advantage. In  order to expand more detailed research in this area, we  propose a new functional versatility framework and measure  model, based on our theoretical analysis. This design should  be used as a basis for constructing a realistic scale for the  evaluation of versatility. A possible path of study arising from  this examination is mentioned in the concluding section of the  report. We concentrate on examining how the development  and utilisation of human resources is incorporated into flexible  organising strategies for human reserves.
Keywords: Flexibility; Functional flexibility; Measurement model; Strategic human resource management; Theoretical review